2019
DOI: 10.3892/or.2019.7195
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive evaluation of FKBP10 expression and its prognostic potential in gastric cancer

Abstract: FK506 binding protein 10 (FKBP10) has been reported to be dysregulated in numerous types of cancer; however, few reports have investigated FKBP10 in gastric cancer (GC). The aim of the present study was to investigate FKBP10 expression in GC and to analyze its association with the prognosis of patients with GC. FKBP10 mRNA expression was evaluated using The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases. The standardized mean differences of the meta-analysis were comprehensively evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 41 publications
3
26
0
Order By: Relevance
“…Olesen et al found that FKBP10 was overexpressed not only in colorectal cancer (CRC) but also in precancerous lesions consisting of hyperplastic polyps, benign tubular adenomas, or tubulo-villous adenomas from the same patients, suggesting a possible involvement of FKBP10 in CRC genesis [ 21 ]. FKBP10 was also found to be upregulated in KRAS-mutant lung adenocarcinoma, renal cell carcinoma, and gastric cancer, and knockdown of FKBP10 is sufficient to hinder proliferation of tumor cells growth [ 18 20 ]. In coincidence with these observations, our study showed that FKBP10 highly expressed in glioma tissues, and knockdown of FKBP10 could inhibit the proliferation of glioma cells both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Olesen et al found that FKBP10 was overexpressed not only in colorectal cancer (CRC) but also in precancerous lesions consisting of hyperplastic polyps, benign tubular adenomas, or tubulo-villous adenomas from the same patients, suggesting a possible involvement of FKBP10 in CRC genesis [ 21 ]. FKBP10 was also found to be upregulated in KRAS-mutant lung adenocarcinoma, renal cell carcinoma, and gastric cancer, and knockdown of FKBP10 is sufficient to hinder proliferation of tumor cells growth [ 18 20 ]. In coincidence with these observations, our study showed that FKBP10 highly expressed in glioma tissues, and knockdown of FKBP10 could inhibit the proliferation of glioma cells both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Nintedanib approved for idiopathic pulmonary fibrosis therapy significantly could down-regulate FKBP10 expression in IPF fibroblasts [ 17 ]. Besides, FKBP10 upregulation has been observed in KRAS mutation-induced lung adenocarcinoma, colorectal cancer renal cell carcinoma, gastric cancer and knockdown of FKBP10 expression could reverse the malignant phenotype, especially proliferation ability [ 18 21 ]. Thus, FKBP10 is an important molecule in cell biology activities and a potential therapeutic target with therapeutic drug.…”
Section: Introductionmentioning
confidence: 99%
“…27 However, compared with benign tumor cells and ovarian epithelial cells, the expression of FK506-binding protein 65 (FKBP65) is decreased in epithelial ovarian cancer cells. 28 FKBP10 is highly expressed in GC, and is a poor prognostic factor for GC; 15 however, the specific mechanism underlying these actions still remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that FKBP10 is highly expressed in a variety of tumors, that it promotes tumor progression and is a poor prognostic factor for tumors, such as kidney, 12 lung 13 and prostate cancer. 14 Online data have shown that FKBP10 is a poor prognostic factor for GC, and that it participate in regulating cell adhesion of GC; 15 however, its specific mechanisms in GC are still unclear. In this study, we performed differential expression gene screening on four independent GC databases, and verified the prognostic effects of 89 consistently up-regulated genes, finally obtaining 12 prognostic genes.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate a mechanism relying on the ribosome binding protein, FKBP10, adapted by cancer cells to support their growth by an increase in the protein synthesis. Hence, this could be a promising target for new anticancer therapy (Liang et al, 2019).…”
Section: Ribosome Modification-related Diseasesmentioning
confidence: 99%